The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fvets.2019.00266
|View full text |Cite
|
Sign up to set email alerts
|

Owner and Cat-Related Risk Factors for Feline Overweight or Obesity

Abstract: Feline obesity is a highly prevalent disease that poses an urgent and serious challenge. Attempted treatment by weight reduction is often unsuccessful; a new preventative approach that focuses on the role of the owner may be helpful. This study used data collected from an international survey of cat owners designed to assess owner personality and self-control, owner-pet attachment, feeding practices, and the cat's body condition. Owner-reported body condition scores (BCS) of cats were assessed using images ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 68 publications
(83 reference statements)
3
43
2
Order By: Relevance
“…One novel finding of our study is the association between increased BCS and the consumption of dry food, which has previously been observed in cats (19,20) but not in dogs (3,11). Specifically, we found that, compared to fresh food, dry food is significantly associated with overweightness/obesity, both alone and in combination with canned or fresh food.…”
Section: Discussionsupporting
confidence: 62%
“…One novel finding of our study is the association between increased BCS and the consumption of dry food, which has previously been observed in cats (19,20) but not in dogs (3,11). Specifically, we found that, compared to fresh food, dry food is significantly associated with overweightness/obesity, both alone and in combination with canned or fresh food.…”
Section: Discussionsupporting
confidence: 62%
“…Conversely, owners reporting outdoor management were more likely to characterize their cats with the standard score. This result corroborated previous studies indicating that indoor cats were frequently associated with obesity, given the lack of stimulation and environmental predictability, which leads to a lower level of physical activity [22,23,43]. Another possible explanation could be that owners of indoor cats provided more treats as gifts, since they reported buying things for the cat more frequently, including sachets and snacks, in addition to toys, beds, or other gifts.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, it might lead to fear and anxiety, behavioral problems, and conflicts with conspecifics in multi-cat indoor environments [20,51,[66][67][68]. Other risks for cats kept exclusively indoors are obesity and domestic accidents [22,23,43]. In turn, whereas an extensive management style should present some benefits by stimulating natural behaviors, it also might impose risks if the care practices and necessity of protection are not considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimates suggest 12-63% of pet cats are overweight or obese [2,[142][143][144][145][146][147]. Feline obesity is associated with multiple comorbidities, most notably diabetes mellitus and hepatic lipidosis [143,[148][149][150][151][152][153].…”
Section: Feline Obesity and Associated Diseasementioning
confidence: 99%